First measurements on the Timespot1 ASIC: a fast-timing, high-rate pixel-matrix front-end. (1st March 2022) - Piccolo, L.; Cadeddu, S.; Frontini, L.; Lai, A.; Liberali, V.; Rivetti, A.; Stabile, A.
Abstract: This work presents the first measurements performed on the Timespot1 ASIC. As the second prototype developed for the TimeSPOT project, the ASIC features a 32 × 32 channels hybrid-pixel matrix. Targeted to space-time tracking applications in High Energy Physics experiments, the system aims to achieve a time resolution of 30 ps or better at a maximum event rate of 3 MHz/channel with a data driven interface. Power consumption can be programmed to range between 1.2 W/cm 2 and 2.6 W/cm 2 . The presented results include a description of the ASIC operation and a first characterization of its performance in terms of time resolution.